The Knowledge Level and The Obedience of Maternal in Undertaking HIV Test - Ucik Rochmayanti; Ismoedijanto Ismoedijanto; Ernawati Ernawati (Health Notions, 2018)
Based on the data of Surabaya Health Office, in 2015 there were 30% of PITC from 55800 maternal and 37 of them were found HIV positive. This percentage has not had obvious explanation. This study aimed to analyze the correlation between the knowledge and the obedience of maternal in undertaking HIV test”. This was analytic observational research by applying cross sectional design in 3 different community health center with high HIV rates. They were community health centre Dupak, Jagir, and Perak. Sample was selected by systematic random sampling. The number of pregnant mother was 80 that undertook ANC in those community health centre. The result showed that 90% of pregnant mother had good knowledge. Statistic test used Fisher exact test showed that the p-value < 0.05 (knowledge level had correlation with the obedience of undertaking HIV test). Keywords: HIV test, Knowledge, Maternal, Obidience.